2020
DOI: 10.1016/j.isci.2020.101008
|View full text |Cite
|
Sign up to set email alerts
|

Ancestrally Duplicated Conserved Noncoding Element Suggests Dual Regulatory Roles of HOTAIR in cis and trans

Abstract: HIGHLIGHTSTwo conserved noncoding elements (CNEs) overlap HOTAIR and its paralog on HOXD cluster Paralog on HOXD cluster may resolve controversy over cis and trans effects of HOTAIR CNEs are positively coregulated with cis HOX genes but negatively with trans cluster Transcribed CNEs with coevolved complementarity suggest hybridization-based function

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…More than 1000 of these non-coding RNAs are persistently conserved from generation to generation [22]. Lately, the conserved DNA non-coding elements (CNE) and their long noncoding RNAs (lncRNA) have been intensively studied by many groups with the help of sophisticated numerical analysis methods [23,24]. Their findings are impressive.…”
Section: A)the Traditional Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…More than 1000 of these non-coding RNAs are persistently conserved from generation to generation [22]. Lately, the conserved DNA non-coding elements (CNE) and their long noncoding RNAs (lncRNA) have been intensively studied by many groups with the help of sophisticated numerical analysis methods [23,24]. Their findings are impressive.…”
Section: A)the Traditional Approachmentioning
confidence: 99%
“…The CNEs play different roles in normal development and disease coordinating spatial-temporal gene expression in both embryos and grown up animals. A CNE that has been thoroughly studied is Hotair which is a lncRNA located between HOXC11 and HOXC12 in the vertebrate chromosome 12 [24]. In the early studies of CNEs it was reported the striking differences in structure and function of the CNEs occur for various vertebrates, in particular in Humans and mice [25].…”
Section: A)the Traditional Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the region is a “hotspot” for RNA-RNA interactions as identified by computational prediction querying HOTAIR against the entire mRNA transcriptome(22). Interestingly, this “hotspot” overlaps a region within HOTAIR that was found to be conserved across vertebrates (except teleosts) with potential for RNA-RNA interaction with a HOXD transcript(23). HOTAIR RNA-RNA interaction was discovered due to its association with the RNA binding protein (RBP), heterogenous nuclear ribonucleoprotein (hnRNP) B1.…”
Section: Introductionmentioning
confidence: 99%